Mangiferin Ameliorates HFD-Induced NAFLD through Regulation of the AMPK and NLRP3 Inflammasome Signal Pathways - Zhang Yong; Wang Ruiqi; Yao Hongji; Ma Ning; Jiang Chenzuo; Zhou Yu; Xia Zhixuan; Liu Qiang; Liu Qibing; Lu Weiying; Zhang Xiaopo (Journal of Immunology Research)
Nonalcoholic fatty liver disease (NAFLD) is closely related to glycolipid metabolism and liver inflammation. And there is no effective drug approved for its clinical therapy. In this study, we focused on mangiferin (Man) and explored its effects and mechanisms on NAFLD treatment based on the regulation of glycolipid metabolism and anti-inflammatory in vivo and in vitro. The results exhibited that Man can significantly attenuate liver injury, insulin resistance, and glucose tolerance in high-fat diet- (HFD-) induced NAFLD mice and significantly reduce fat accumulation and inflammation in hepatic tissue of NAFLD mice. The transcriptome level RNA-seq analysis showed that the significantly different expression genes between the Man treatment group and the HFD-induced NAFLD model group were mainly related to regulation of energy, metabolism, and inflammation in liver tissue. Furthermore, western blots, real-time PCR, and immunohistochemistry experiments confirmed that Man significantly activated the AMPK signal pathway and inhibited NLRP3 inflammasome activation and pyroptosis in NAFLD mice. In in vitro cell experiments, we further confirmed that Man can promote glucose consumption and reduce intracellular triglyceride (TG) accumulation induced by free fatty acids in HepG2 cells and further that it can be blocked by AMPK-specific inhibitors. Western blot results showed that Man upregulated p-AMPKα levels and exhibited a significant AMPK activation effect, which was blocked by compound C. At the same time, Man downregulated the expression of NLRP3 inflammasome-related proteins and inhibited the activation of NLRP3 inflammasome, alleviating cell pyroptosis and inflammation effects. These results indicate that Man anti-NAFLD activity is mediated through its regulation of glucolipid metabolism by AMPK activation and its anti-inflammatory effects by NLRP3 inflammasome inhibition. Our study indicates that Man is a promising prodrug for the therapy of NAFLD patients.